2021
DOI: 10.1021/acs.est.0c02015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Mechanical Abrasion of MWCNT Nanocomposites Used in 3D Printing: Influence of CNT Content on Abrasion Products and Rate of Microplastic Production

Abstract: Manufactured nanomaterials (MNMs) are incorporated as “nanofillers” into consumer products to enhance properties of interest. Multiwalled carbon nanotubes (MWCNTs) are known for their unique properties and have many applications in polymers. However, the release of MWCNTs during the nanoenabled product life cycle is concerning. During the use phase, mechanical stresses can produce fragmented materials containing MNMs. The degree of MNM release, the resulting exposure to these materials, and the potential impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…To simulate abrasion conditions representative of actual product use, further methods development and studies will be required; this initial standard method was applied as proof of concept, in line with work on other product matrices. Using methods and equations from Sipe et al and Bossa et al [ 19 , 22 ], the abrasion rate was calculated in units of grams released per surface area of product tested over time (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To simulate abrasion conditions representative of actual product use, further methods development and studies will be required; this initial standard method was applied as proof of concept, in line with work on other product matrices. Using methods and equations from Sipe et al and Bossa et al [ 19 , 22 ], the abrasion rate was calculated in units of grams released per surface area of product tested over time (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Potter et al [44] pointed out that carbon nanotubes (CNTs) are added to 3D printer filaments to increase their conductivity. Bossa et al [63] studied polymers for 3D printing containing MWCNTs (multiwall carbon nanotubes) and found that microplastics are released through abrasion. Overall, the chemical composition of particles produced by 3D printing is very heterogeneous and influenced by the filament, the chemicals in the printer itself, and its operating conditions.…”
Section: Indoor Sources Of Microplasticsmentioning
confidence: 99%
“…Effects that nanopollution exacts on human health and the environment generated from the production and application of nanomaterials have been a pressing problem to be solved. Multiwalled carbon nanotubes (MWCNTs), a kind of nanomaterial that excels in mechanical, electrical, and magnetic properties, are widely used in high-tech fields including electronics, structural engineering, medicine, and hydrogen fuel cells. Due to the increase in MWCNTs production, humans are under a growing risk of being exposed to MWCNTs, especially the pathway of environmental exposure. , It is reported that the global demand for carbon nanotubes will reach >50,000 tons per year in a few years, which causes widespread concerns about whether MWCNTs will endanger our health. MWCNT-7 was classified as “possibly carcinogenic to humans” (Group 2B) in 2014 and added to the SIN List in 2019. , The existence of carbon nanotubes in bronchoalveolar lavage fluid (BALF) or lung cells from victims of the 2001 World Trade Center attack and asthmatic Parisian children highlights the reality of chronic carbon nanotube exposure and toxicity. , Hence, it is important to assess the potential adverse health effects of MWCNTs via environmental or occupational exposure.…”
Section: Introductionmentioning
confidence: 99%